Islamic Justice In A Monetary System - Muhammad Anwar (International Institute of Islamic Thought, 1987)
Dr. M. Umer Chapra. Towards a Just Monetary System. Leicester: The Islamic Foundation. 1985. 292p. Extensive literature on the institutional aspects of monetary economics includes pioneering studies by Muhammad Uzair, Muhammad Nejatullah Siddiqi, Ziauddin Ahmed, Anwar Iqbal Qureshi, Afzalur Rahman, and the Council of Islamic Ideology in Pakistan among many others. Scores of research papers have elaborated the functioning of Islamic banking in theory and practice. A fresh study on Islamic banking in Iran and Pakistan by Zubair Iqbal and Abbass Mirakhor has been released by the International Monetary Fund. In the voluminous literature on issues dealing with money and banking in Islam, Towards Q Just Monetary System is outstanding in many respects. The study is tightly knit, thoroughly documented, and the ideas are careklly analyzed. These qualities are lacking in most works on Islamic economics. Competence in ecnomics and command of Arabic for access to original sources in Islam is essential for a scholarly integration of shari'ah and modem economic analysis in order to address ContempOrary economic problems. There is no doubt that Dr. Umer Chapra, Economic Adviser to the Saudi Arabian Monetary Agency, has all the necessary background. Towards a Just Monetary System introduces a perspective on the interestbearing system before outlining various socio-economic goals and strategies in chapter one. Islamic views on the nature of riba are discussed in chapter two supported by a comprehensive appendix based on the Qur'an, Ahadith, and Fiqh literature on riba. Equity-based financing as an alternative to interest-based financing is proposed in chapter three, for which necessary reforms are outlined in chapter four. A vigorous comparison is drawn in chapter five between interest-bearing and interest-free systems in terms of allocation of resources, saving and capital formation, stability, economic growth, and fulfilment of various types of credit needs. Some necessary ...